The choice of the optimal experimental model of myocardial infarction - V. V. Koval'skaja; I. V. Savytskyi; A. A. Mironov (Kazimierz Wielki University, 2017)
Nowadays myocardial infarction has a high percentage of mortality [12], and is widespread inUkraine and Western countries [1, 2, 3]. Such a situation calls for the development of a new model of myocardial infarction, which would be as simple and effective as possible. In this article, a model of myocardial infarction with the use of inhalation anesthesia with chloroform is proposed.